2010
DOI: 10.1590/s1413-86702010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of pathogenic yeasts in the air from hospital environments in the city of Fortaleza, northeast Brazil

Abstract: This paper reports the results of environmental surveillance of yeasts in specific areas of two tertiary local hospitals. From March 2007 to February 2008, samples from the air of two public hospitals were collected on a monthly basis. The samples were collected through passive sedimentation method (day and night exposure) of Petri dishes. A total of 240 air samples from 10 hospital environments were analyzed. These environments presented similar contamination levels, from which 80 fungi isolates were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
17
0
5
Order By: Relevance
“…(2) Vários estudos sugerem que a distribuição de fungos no ar, em termos quantitativos e qualitativos, varia entre áreas geográficas, e também é influenciada por fatores ambientais, sazonais e fatores climáticos, tais como temperatura, umidade do ar, hora do dia, velocidade e direção do vento, presença de atividade humana e tipo de ventilação em ambientes fechados. (3) Candida albicans é um fungo dimórfico, que se apresenta sob formas leveduriformes (blastoconídios) no estado saprofítico, estando associado à colonização assintomática, ou como formas filamentosas (pseudo-hifas e hifas verdadeiras), observadas em processos patogênicos. Além disso, sob condições de crescimento subótimas, nesse fungo pode ocorrer a formação de clamidósporos (esporos arredondados que possuem uma espessa parede celular).…”
Section: Introductionunclassified
“…(2) Vários estudos sugerem que a distribuição de fungos no ar, em termos quantitativos e qualitativos, varia entre áreas geográficas, e também é influenciada por fatores ambientais, sazonais e fatores climáticos, tais como temperatura, umidade do ar, hora do dia, velocidade e direção do vento, presença de atividade humana e tipo de ventilação em ambientes fechados. (3) Candida albicans é um fungo dimórfico, que se apresenta sob formas leveduriformes (blastoconídios) no estado saprofítico, estando associado à colonização assintomática, ou como formas filamentosas (pseudo-hifas e hifas verdadeiras), observadas em processos patogênicos. Além disso, sob condições de crescimento subótimas, nesse fungo pode ocorrer a formação de clamidósporos (esporos arredondados que possuem uma espessa parede celular).…”
Section: Introductionunclassified
“…Nosocomial infections are one of the problems in recent decades especially in the wards where immunocompromised patients are hospitalized (1,2). Bio-aerosols in the hospital air are one of the potential sources of infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…and Acremonium spp. (1,3,4). Yeast isolates have also been found that belong to the genus of Candida, Trichosporon, Rhodotorula, Saccharomyces, and Cryptococcus (1,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous results from our laboratory (Varo et al 2007, Pires-Gonçalves et al 2008, Candida parapsilosis was shown to be the predominant yeast involved in the contamination of water samples collected from a haemodialysis centre. In addition, C. parapsilosis has emerged as a major pathogen in nosocomial candidemia in Brazilian tertiary care hospitals (Medrano et al 2006, Bruder-Nascimento et al 2010, Cordeiro et al 2010, Pereira et al 2010. Recently, the C. parapsilosis complex has been redefined as three distinct species: C. parapsilosis, Candida orthopsilosis and Candida metapsilosis (Tavanti et al 2005); however, the current literature contains very little data pertaining to the distributions and antifungal susceptibilities of these biofilm Candida species.…”
mentioning
confidence: 99%